The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1997
DOI: 10.1073/pnas.94.25.13873
|View full text |Cite
|
Sign up to set email alerts
|

Both hypertrophic and dilated cardiomyopathies are caused by mutation of the same gene, δ-sarcoglycan, in hamster: An animal model of disrupted dystrophin-associated glycoprotein complex

Abstract: Cardiomyopathy (CM) is a primary degenerative disease of myocardium and is traditionally categorized into hypertrophic and dilated CMs (HCM and DCM) according to its gross appearance. Cardiomyopathic hamster (CM hamster), a representative model of human hereditary CM, has HCM and DCM inbred sublines, both of which descend from the same ancestor. Herein we show that both HCM and DCM hamsters share a common defect in a gene for ␦-sarcoglycan (␦-SG), the functional role of which is yet to be characterized. A brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
229
3
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 281 publications
(242 citation statements)
references
References 27 publications
9
229
3
1
Order By: Relevance
“…Analysis of skeletal muscle tissue biopsies from these patients reveals the loss or dramatic reductions in the expression of all the sarcoglycans when there is a disease-related mutation in a single sarcoglycan family member. The interdependence of sarcoglycan expression is also evident from studies employing sarcoglycan-null mouse models, although cardiac abnormalities are found in only ␤-, ␦-, and ␥-sarcoglycan-null mice (47)(48)(49)(50). Unlike these sarcoglycan-null mouse models, Cav-3 KO mice show no changes in expression or overall membrane localization of the sarcoglycans.…”
Section: Discussionmentioning
confidence: 78%
“…Analysis of skeletal muscle tissue biopsies from these patients reveals the loss or dramatic reductions in the expression of all the sarcoglycans when there is a disease-related mutation in a single sarcoglycan family member. The interdependence of sarcoglycan expression is also evident from studies employing sarcoglycan-null mouse models, although cardiac abnormalities are found in only ␤-, ␦-, and ␥-sarcoglycan-null mice (47)(48)(49)(50). Unlike these sarcoglycan-null mouse models, Cav-3 KO mice show no changes in expression or overall membrane localization of the sarcoglycans.…”
Section: Discussionmentioning
confidence: 78%
“…Recently, single gene defects that cause familial DCM (Ϸ25-30% of idiopathic DCM) have been identified for cytoskeletal (dystrophin, desmin, tafazzin, and ␦-sarcogycan) and sarcomeric (actin, tropomyosin, myosin, and troponin T) proteins (26,(39)(40)(41)(42)(43)(44)(45). Mutations in cytoskeletal proteins imply that deficits in transmission of force generated by sarcomere may be one mechanism for the pathogenesis of DCM.…”
Section: Discussionmentioning
confidence: 99%
“…All the CM hamsters share the genomic deletion of about 30-kb interval, which includes the two promoters and first exons of delta-sarcoglycan gene with consequent loss of its protein product [212,248,249]. The consequences of the genetic loss of delta-sarcoglycan in heart are related not only to sarcolemmal fragility but also to coronary vasospasm from disruption of dystrophin-associated protein complex [44].…”
Section: Syrian Cardiomyopathic Hamstermentioning
confidence: 99%